A perspective on the role of physiological stresses in cancer, diabetes and cognitive disease as environmental diseases - Esterhuizen, Maranda; Park, Chang-Beom; Kim, Young Jun; Kim, Tae-Young; Yoon, Hakwon; Andres, Frederic; Rodriguez-Rodriguez, Rosalia; Tanabe, Shihori (Frontiers in Molecular Biosciences, 2023)
With rapid industrialization, urbanization, and climate change, the impact of environmental factors on human health is becoming increasingly evident and understanding the complex mechanisms involved is vital from a healthcare perspective. Nevertheless, the relationship between physiological stress resulting from environmental stressors and environmental disease is complex and not well understood. Chronic exposure to environmental stressors, such as air and water contaminants, pesticides, and toxic metals, has been recognized as a potent elicitor of physiological responses ranging from systemic inflammation to immune system dysregulation causing or progressing environmental diseases. Conversely, physiological stress can exacerbate susceptibility to environmental diseases. Stress-induced alterations in immune function and hormonal balance may impair the ability to detoxify harmful substances and combat pathogens. Additionally, prolonged stress can impact lifestyle choices, leading to harmful behaviors. Understanding the link between physiological stress and environmental disease requires a systematic, multidisciplinary approach. Addressing this complex relationship necessitates the establishment of a global research network. This perspective discusses the intricate interplay between physiological stress and environmental disease, focusing on common environmental diseases, cancer, diabetes, and cognitive degeneration. Furthermore, we highlight the intricate and reciprocal nature of the connection between physiological stress and these environmental diseases giving a perspective on the current state of knowledge as well as identifying where further information is necessary. Recognizing the role of physiological stress in environmental health outcomes will aid in the development of comprehensive strategies to safeguard public health and promote ecological balance.